Fully-autonomous Operation of an AC Micro-grid with Inherent Seamless Switching - Liu, Baoquan; Xu, Mengjie; Chen, Jingwen (Recent Advances in Electrical & Electronic Engineering, 2021)
Background: Conventional micro-grids operate autonomously in islanded mode but they always rely on the utility grid for BUS voltage support and power balance in the grid-connected mode. This results in non-seamless mode switching, alternating operation strategy and power exchange fluctuation problems. Methods: An AC/DC/AC converter is utilized as the interface between the micro-grid and the utility grid. This enables the two entities to have different voltages in the grid-connected mode. The microgrid exchanges predefined amount of power with the utility grid in the grid-connected mode. The power amount is estimated based on power forecasting of local generations and loads with the consideration of the Sate of Charge (SOC) of the battery, and is updated and broadcasted every 15 minutes. Results: A 100kVA AC micro-grid with a rotating generator, battery storage and solar arrays is built on Matlab/Simulink for investigation. Results indicate that the battery can effectively balance the power flow and mode switching hardly causes distortions. Conclusion: The proposed micro-grid can operate autonomously in both grid-connected and islanded mode without relying on the utility grid. Seamless switching between operation modes can be achieved naturally. Constant power is exchanged with the power grid, which benefits the powerdispatching algorithm of the power system.
Keywords: diesel genset